Should we all be feminists? Development of the Liberal Feminist Attitudes Scale - Henze, Bonny-Lycen; Buhl, Sarah; Kolbe, Elisa; Asbrock, Frank (Frontiers in Social Psychology, 2024)
All authors contributed to the study conception and design. Material preparation, data collection and analysis were performed by Bonny-Lycen Henze and Elisa Kolbe. The first draft of the manuscript was written by Bonny-Lycen Henze and all authors commented on previous versions of the manuscript. All authors read and approved the final manuscript.individual and society is a subject of critical scholarly debate, there is a lack of suitable instruments to measure the complexity of modern feminist attitudes. In three studies, we developed a scale assessing liberal feminist attitudes and tested its factor structure and validity. In Study 1, we generated an item pool capturing liberal feminist attitudes and presented it to a sample of N = 473 with scales for Ambivalent Sexism (hostile and benevolent), Social Dominance Orientation, System Justification, Neoliberal Beliefs, and the self-labelling as a feminist. In Studies 2 (N = 310) and 3 (N = 214) we aimed at replicating the factor structure of the LFAS from Study 1 and confirmed the construct and criterion validity with measurements of the constructs Self-Identification as a Feminist, Personal Progress, Conformity to Feminine Norms and a concrete behavioural measure that captured the willingness to receive information about feminism in the future. Exploratory factor analysis (Study 1) yielded a 4-factor structure with 17 itemsthe Liberal Feminist Attitudes Scale (LFAS). In Studies 2 and 3, this 4-factorial model showed excellent model fit, internal consistency and convergent as well as discriminant and criterion validity, at least within a particular demographic (i.e., German students). The LFAS holds the potential to provide psychologists with a tool to examine and analyse liberal feminist attitudes comprehensively.